The role of emergency endoscopy in upper git foreign body extraction: Pomen nujne endoskopije zgornjih prebavil pri odstranitvi tujkov – rezultati obdobja 1994-2008 - Skok, Pavel; Ocepek, Andreja; Ćeranić, Davorin (Acta Medico-Biotechnica, 2021)
Purpose: Foreign bodies in the upper gastrointestinal tract (GIT) rarely cause urgent problems in gastroenterology. The purpose of the study was to assess the percentage of patients in whom urgent endoscopic investigation revealed true foreign bodies in the upper GIT and to evaluate the success of emergency endoscopic procedures. Methods: The study includes patients in whom urgent endoscopic investigations of the upper GIT were performed in the period 1 January 1994 to 1 May 2008. Results: 8552 patients were investigated, average age 60.6 years (SD±17.1 years, range 1–106 years), with 3276 (38 %) females and 5276 males (62 %). In 69 patients (0.8 %), “true” foreign bodies were detected in the esophagus or stomach. In these patients a total of 90 endoscopic investigations were performed: in 65/69 patients (94.2%) the foreign bodies were removed endoscopically; in 4 (5.8 %) cases the endoscopic procedures were unsuccessful. Among the foreign bodies removed were a variety metal or plastic objects, such as coins, keys, screws, hooks, batteries, razor blades, needles, lighters, buttons, and parts of kitchen, toilet or writing utensils. In patients with successful endoscopic removal of the objects, no significant complications were noted. In 4 patients (4/69, 5.8 %) mild hemorrhages from the region of the esophagogastric junction were observed. Conclusion: Endoscopic technologies allow successful removal of a variety of types of foreign bodies from the upper GIT.
Keywords: foreign bodies; upper gastrointestinal tract; endoscopy; extraction; complications